A review of recent clinical trials to evaluate disease-modifying therapies in the treatment of cardiac amyloidosis - Senigarapu, Sindhuja; Driscoll, James J. (Frontiers in Medicine, 2024)
Cardiac amyloidosis (CA) is a serious condition that results in infiltrative cardiomyopathy and heart failure with preserved ejection fraction (HFpEF) that is caused by the extracellular deposition of amyloid fibrils within heart tissue. While many important features of CA have been known for years, its prevalence in elderly patients with HF is increasingly being recognized. Plasma cells produce monoclonal immunoglobulin light chains which results in the formation and aggregation of amyloid fibrils that are responsible for AL amyloidosis. CA is classified as originating from either transthyretin (ATTR) or light chain (AL) amyloidosis. ATTR CA may result from a genetic mutation in the TTR gene, which is inherited (ATTRv), or from age-related deposition from wild-type ATTR (ATTRwt). Cardiac involvement in AL amyloidosis is attributed to either of two mechanisms: the extracellular deposition of amyloid fibril in the myocardium, or direct cardiotoxicity from the fibril aggregates. Typing of amyloid fibrils, a critical determinant of therapy, has also improved with wider availability of laser capture and mass spectrometry of histologic specimens. Specific and accurate evaluation of CA is now possible using cardiac magnetic resonance imaging and bone scintigraphy tracers. Survival in CA has improved markedly as novel chemotherapy agents have become available, but challenges remain in advanced disease. Broadening the amyloid-specific therapeutic landscape to include RNA inhibitors, fibril formation stabilizers and inhibitors, and immunotherapeutic targeting of amyloid deposits holds promise and may improve outcomes in systemic and cardiac amyloidoses. Treatment strategies for CA has recently undergone transformative changes, leading to some progress in outcomes for certain patients. Here, we discuss the basic features of CA as well as the emergence of novel, disease-modifying strategies that have been recently evaluated in clinical trials for the treatment of CA.